2019
DOI: 10.1111/wvn.12354
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Self‐Efficacy in Shaping Self‐Management Behaviors Among Adults With Type 2 Diabetes

Abstract: Background: Self-efficacy, diabetes distress, knowledge, and education level are likely the important factors affecting diabetes self-management (DSM) behaviors. However, the theoretical mechanisms underlying these variables remain unclear. Aims:The study aimed to test a model including variables of self-efficacy, diabetes distress, knowledge, and education level and DSM behaviors that were informed by social cognitive theory and the literature review among adults with type 2 diabetes. Methods:A cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 40 publications
3
27
3
Order By: Relevance
“…In a further analysis of the mediating effect of self-efficacy, we found that a higher education level was related to greater self-efficacy, but this did not translate to improved adherence to self-management. This finding is different from that of a previous study where self-efficacy mediated the association between education level and self-management behaviors [ 31 ]. Further research into the role of self-efficacy in shaping patient adherence to self-management behaviors is warranted.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In a further analysis of the mediating effect of self-efficacy, we found that a higher education level was related to greater self-efficacy, but this did not translate to improved adherence to self-management. This finding is different from that of a previous study where self-efficacy mediated the association between education level and self-management behaviors [ 31 ]. Further research into the role of self-efficacy in shaping patient adherence to self-management behaviors is warranted.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings suggest that self-efficacy in performing self-management may explain the observed differences in patient adherence across these socio-demographic groups. A study that examined the role of self-efficacy in shaping self-management behaviors among diabetic patients reported that self-efficacy partially explained the association of diabetes knowledge with adherence and fully explained the association of distress and education level with adherence [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The classic HBM has been use in research on the adoption of preventive health behavior in several chronic and contagious diseases [ 46 , 47 ]. This model suggests that individuals will take action when a disease poses a serious threat and there are practices that could prevent the disease.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a follow-up study by Williams et al, demonstrated that smoking and physical activity partly mediated the association between education and the development of DMT2 [ 49 ]. Moreover, self-efficacy may mediate the effect between education and DMT2 self-management behaviors [ 46 ]. In a study of the influenza A virus subtype H [Hemagglutinin] 1 N [Neuraminidases] 1 (H1N1) epidemic in Canada, the association between hospitalization for the disease and known risk factors, such as high body mass index, smoking, and antiviral therapy could not fully mediate the association between H1N1 hospitalizations with socioeconomic variables.…”
Section: Discussionmentioning
confidence: 99%
“…T2D self-management is thought to be associated with self-efficacy (Jiang et al, 2019). Jiang and colleagues found that self-efficacy has the strongest direct impact on T2D selfmanagement.…”
mentioning
confidence: 99%